4(b-2.1)=b+0.6

Simple and best practice solution for 4(b-2.1)=b+0.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(b-2.1)=b+0.6 equation:


4 (b-2.1)=b + 0.6

We simplify the equation to the form, which is simple to understand
4(b-2.1)=b + 0.6

Reorder the terms in parentheses
+(+4b-8.4)=b + 0.6

Remove unnecessary parentheses
+4b-8.4=+b + 0.6

We move all terms containing b to the left and all other terms to the right.
+4b-1b=0.6+8.4

We simplify left and right side of the equation.
+3b=+9

We divide both sides of the equation by 3 to get b.
b=3

See similar equations:

| 3(3n-y)+1=31 | | (3r+8)(3r-8)= | | 2x^2-7=59 | | 7y=-4x | | 2(x+4)+2=8x+2(x+2) | | (7x+84)=112 | | 3x+2x-2=4x+x+2 | | -0.2-q=9q | | X*.05833333333=(X-113) | | N^7/10 | | 2g+3G=10 | | 4(-y+2)=-1 | | X/3=70 | | N^10/7 | | 2m+-3m-8=26 | | Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 |

Equations solver categories